2021
DOI: 10.1093/ijpp/riab031
|View full text |Cite
|
Sign up to set email alerts
|

Validation of neonatal and paediatric antimicrobial stewardship treatment algorithms in rapid diagnostic-detected bacteraemia

Abstract: Objectives Blood culture rapid diagnostic testing (RDT) aids in early organism identification and resistance gene detection. This information allows quicker transition to tailored antimicrobial therapy, improved patient outcomes and prevention of antimicrobial resistance. An antimicrobial treatment algorithm based on RDT results and local antibiograms can serve as a valuable clinical decision-support tool. This study assessed the proportion of appropriate antibiotic therapy recommendations us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…On the other hand, if LOS is suspected, cultures should be obtained from two separate sites to ensure that the bacterial growth represents a true infection rather than a contaminant [ 35 ]. Recent data have shown that a specific algorithm-guided treatment might allow clinicians to reduce the misuse of antimicrobial drugs, as demonstrated in a retrospective, observational study conducted in a neonatal and pediatric population in the USA [ 84 ]. A specific algorithm based on multivariate models (i.e., Neonatal Early-Onset Sepsis Calculator) may be used to assess the early-onset Group B streptococcal (GBS) infection risk in infants >35 weeks gestational age [ 85 , 86 ].…”
Section: Antimicrobial Stewardshipmentioning
confidence: 99%
“…On the other hand, if LOS is suspected, cultures should be obtained from two separate sites to ensure that the bacterial growth represents a true infection rather than a contaminant [ 35 ]. Recent data have shown that a specific algorithm-guided treatment might allow clinicians to reduce the misuse of antimicrobial drugs, as demonstrated in a retrospective, observational study conducted in a neonatal and pediatric population in the USA [ 84 ]. A specific algorithm based on multivariate models (i.e., Neonatal Early-Onset Sepsis Calculator) may be used to assess the early-onset Group B streptococcal (GBS) infection risk in infants >35 weeks gestational age [ 85 , 86 ].…”
Section: Antimicrobial Stewardshipmentioning
confidence: 99%